High production of 2,3-butanediol from glycerol without 1,3-propanediol formation by Raoultella ornithinolytica B6 - Kim, Tae yeon; Cho, Sukhyeong; Woo, Han Min; Lee, Sun-Mi; Lee, Jinwon; Um, Youngsoon; Seo, Jin-Ho (Springer Verlag, 2017)
Conversion of crude glycerol derived from biodiesel processes to value-added chemicals has attracted much attention. Herein, Raoultella ornithinolytica B6 was investigated for the high production of 2,3-butanediol (2,3-BD) from glycerol without 1,3-propanediol (1,3-PD) formation, a by-product hindering 2,3-BD purification. By evaluating the effects of temperature, agitation speed, and pH control strategy, the fermentation conditions favoring 2,3-BD production were found to be 25 A degrees C, 400 rpm, and pH control with a lower limit of 5.5, respectively. Notably, significant pH fluctuations which positively affect 2,3-BD production were generated by simply controlling the lower pH limit at 5.5. In fed-batch fermentation under those conditions, R. ornithinolytica B6 produced 2,3-BD up to 79.25 g/L, and further enhancement of 2,3-BD production (89.45 g/L) was achieved by overexpressing homologous 2,3-BD synthesis genes (the budABC). When pretreated crude glycerol was used as a sole carbon source, R. ornithinolytica B6 overexpressing budABC produced 78.10 g/L of 2,3-BD with the yield of 0.42 g/g and the productivity of 0.62 g/L/h. The 2,3-BD titer, yield, and productivity values obtained in this study are the highest 2,3-BD production from glycerol among 1,3-PD synthesis-deficient 2,3-BD producers, demonstrating R. ornithinolytica B6 as a promising 2,3-BD producer from glycerol.